Joining Application of Unmanned Aerial Vehicle Imagery with GIS for Monitoring of Soft Cliff Linear Habitats - Egidijus Jurkus; Julius Taminskas; Ramūnas Povilanskas; Arvydas Urbis; Jovita Mėžinė; Domantas Urbis (Journal of Marine Science and Engineering)
In the coastal zone, two types of habitats—linear and areal—are distinguished. The main differences between both types are their shape and structure and the hydro- and litho-dynamic, salinity, and ecological gradients. Studying linear littoral habitats is essential for interpreting the ’coastal squeeze’ effect. The study’s main objective was to assess short-term behavior of soft cliffs as littoral linear habitats during calm season storm events in the example of the Olandų Kepurė cliff, located on a peri-urban protected seashore (Baltic Sea, Lithuania). The approach combined the surveillance of the cliff using unmanned aerial vehicles (UAVs) with the data analysis using an ArcGIS algorithm specially adjusted for linear habitats. The authors discerned two short-term behavior forms—cliff base cavities and scarp slumps. The scarp slumps are more widely spread. It is particularly noticeable at the beginning of the spring–summer period when the difference between the occurrence of both forms is 3.5 times. In contrast, cliff base cavities proliferate in spring. This phenomenon might be related to a seasonal Baltic Sea level rise. The main conclusion is that 55 m long cliff cells are optimal for analyzing short-term cliff behavior using UAV and GIS.